MANAGEMENT OF CEKKENG MARKET LEVIES IN INCREASING OF THE ORIGINAL REGIONAL INCOME OF BULUKUMBA REGENCY - Irnayanti Irnayanti; Herlina Sakawati; Oky Nur Pratiwi Johansyah; Putri Dzakilla Handayani (Universitas Negeri Makassar, 2026)
This research aims to determine the Management of Cekkeng Market Retribution in Increasing Original Regional Income of Bulukumba Regency. This research uses a qualitative approach and produces descriptive data. Data collection was used using interview, documentation and observation techniques. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The results of the research show that the Management of Cekkeng Market Retribution in Increasing Original Regional Income of Bulukumba Regency is based on Mardiasmo (2018) management indicators, namely: 1) planning and preparation stage, 2) ratification stage, 3) implementation stage, 4) reporting and evaluation stage, that in general In general, market levy management is quite good, but it needs to be optimized in terms of the planning and preparation stages as well as the implementation stage in order to avoid problems that could affect regional income.